Doctors' understanding of consent law. Issue 7 (18th July 2021) - Skiba, Rohen; Sikotra, Nisha; Wilson, Alexandra; Clay, Timothy D.; Gabbay, Eli
Abstract: Background: Obtaining informed consent is an important responsibility of all doctors and is a major component of their day‐to‐day practice. However, little is known regarding practising doctors' understanding of consent in relation to medical law. Aims: To gain insights into current doctors' understanding of the legal requisites that underpin the consent of patients to medical procedures in Australia. Methods: A cross‐sectional survey of Western Australian medical practitioners was conducted. A 15‐question online questionnaire (SurveyMonkey, USA) was developed and distributed to Western Australia medical practitioners via social media, hospital‐based Junior doctor society pages and through the email accounts of practitioners registered with MDA National ‐ a large medical defence organisation. Doctors were questioned on their understanding of medicolegal responsibilities, informed consent practice and knowledge of a historically significant Australian medicolegal case (Rogers v Whitaker, 1992). Results: A total of 172 responses was received during the survey period. The respondents came from various levels of seniority and from a variety of subspecialist areas. The survey demonstrated that among the respondents, the understanding of their medicolegal responsibilities around the issues of informed consent was deficient. Only 31% of respondents were aware that it is a court of law that defines the reasonable standard of care in relation to obtaining informed consent. Less than half of the respondents (48%) were aware of the High Court of Australia's definition by which the standard of reasonable care is defined. Conclusion: The results from our survey suggest that there is a requirement to enhance the education of medical practitioners to meet the medicolegal requirements and optimise consent.